Hambatan Majelis Jemaat dalam Mengatasi Kekerasan dalam Rumah Tangga di PJM-PB Jemaat Korampotan Pondan - Naulu, Letisia; Mosooli, Ermin Alperiana; Sopang, Oskar (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2022)
Domestic violence (KDRT) causes misery for victims, especially women and children. Therefore the church needs to be involved in efforts to overcome it. But the fact is that churches, in general, haven't done much about domestic violence. This research seeks to discover the church's obstacles in overcoming domestic violence through research in the Persekutuan Jemaat Mandiri Protestan Banggai (PJM-PB) Korampotan Pondan congregation. The method used is qualitative, with interviews as a data collection technique. Data were analyzed with reduction, display, and conclusions techniques. The results show two dominant obstacles for the MPH Congregation in overcoming domestic violence: 1) cultural factors, namely values that perceive domestic violence as a private family matter that others should not know about and interfere with; 2) lack of knowledge about domestic violence. The theological factors usually an obstacle for the church are not found in this study.